De Russische vertalingen van Andreas Vesalius’ (1514-1564) anatomische werken - Biesbrouck, Maurits; Goddeeris, Theodoor; Steeno, Omer (Studium, 2016)
History of the translation of Andreas Vesalius’s anatomical works into RussianAn important contribution to the scientific reform of medicine in Russia in the seventeenth century was the translation into Russian of the Epitome, a short anatomical work by Andreas Vesalius (1514-1564). We will reconstruct the history of this translation by Epifani Slavinetski (±1609-1675), as well as the search for the original work used for it. We will also present the history of the very first vernacular translation of Vesalius’s De Humani Corporis Fabrica, published in Russia in 1950-1954, and of another translation of the Epitome into Russian in 1974.